Novel Deep Space Nuclear Electric Propulsion Spacecraft. (3rd June 2021) - Howe, Troy; Howe, Steve; Miller, Jack
Abstract: The space industry is expanding at an increasing rate. While most efforts are currently focused on Earth and lunar orbits, it is only a matter of time before affordable exploration missions into deep space become more prevalent. Nuclear electric propulsion (NEP) with large quantities of power have been theorized for such missions with many advantages over traditional solar panels and radioisotope power sources. Key among NEP issues has been the power conversion system, often falling upon dynamic cycles over solid-state options like thermoelectric generators (TEGs) because of low efficiencies. Howe Industries has conceptualized a deep space probe capable of transporting cube satellites (CubeSats) and other payloads to deep space utilizing NEP based on an advanced TEG power conversion system with efficiencies that would challenge traditional dynamic power conversion cycles. Experimentation at a TRIGA research reactor has shown a potential for 20 to 50 times increase in electrical conductivity of potential thermoelectric materials, which would correlate to large increases in efficiencies over traditional TEGs.